CLASSROOM INTERACTION IN COMMUNICATIVE LANGUAGE TEACHING OF SECONDARY SCHOOL - Novi Lesiana; Mulyadi; Aswadi Jaya; Etty Pratiwi (Universitas PGRI Palembang, 2024)
This research aimed to describe the dynamics of classroom interaction and examine the factors influencing it. The researcher utilized qualitative methods, including classroom observation, semi-structured interviews, and questionnaires. The findings revealed that the teacher predominantly led and controlled the interaction. Good interaction only occurs at the beginning of the lesson, so for the most part, the teacher initiates and the students only responded to the teacher by giving answers in the form of phrases or words. For interaction between students they are interacted with their friends most of the time. But, mostly, it was not related to the English topic discussed. The researcher also found several factors affecting classroom interaction, such as students' lack of motivation, hesitancy to speak and engage in class discussions due to limited vocabulary, embarrassment, and fear of making mistakes.